2018
DOI: 10.1021/acs.iecr.8b01547
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Nearby Hydroxyls’ Role in Promoting HCHO Oxidation over a Pt Catalyst

Abstract: Insight into the relationship between catalytic trends and physicochemical properties of composite nanoparticles is essential for their rational design. Herein, a series of 3d-M (M = Mn, Fe, Co, Ni) metal hydroxidepromoted PtM(OH) x /Al 2 O 3 catalysts are developed and well characterized for establishing the catalytic HCHO oxidation reactivity trend as a function of more fundamental properties, such as hydroxyl concentration and adsorption strength. The reactivity of PtM(OH) x /Al 2 O 3 exhibits an increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Several methods have been applied for the removal of HCHO, including adsorption, photocatalysis, plasma technology, and catalytic oxidation. Adsorption is the most widely used method for indoor air HCHO removal, but it suffers from limited adsorption capacities of absorbents and secondary pollution during regeneration . Because HCHO can be completely oxidized to form H 2 O and CO 2 by catalytic oxidation without other byproducts, this method is now regarded as one of the most promising candidate technologies for indoor air HCHO elimination. , Transition metal oxides (Co, Ni, Ag, and Mn) and supported noble metal (Pt, Pd, Rh, and Au) catalysts have been widely investigated for HCHO oxidation. Generally, the transition metal oxides require high temperatures (>100 °C) to achieve complete oxidation of HCHO.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been applied for the removal of HCHO, including adsorption, photocatalysis, plasma technology, and catalytic oxidation. Adsorption is the most widely used method for indoor air HCHO removal, but it suffers from limited adsorption capacities of absorbents and secondary pollution during regeneration . Because HCHO can be completely oxidized to form H 2 O and CO 2 by catalytic oxidation without other byproducts, this method is now regarded as one of the most promising candidate technologies for indoor air HCHO elimination. , Transition metal oxides (Co, Ni, Ag, and Mn) and supported noble metal (Pt, Pd, Rh, and Au) catalysts have been widely investigated for HCHO oxidation. Generally, the transition metal oxides require high temperatures (>100 °C) to achieve complete oxidation of HCHO.…”
Section: Introductionmentioning
confidence: 99%
“…The main active ingredient of diesel exhaust purification catalysts in practice is still Pt nanocatalysts. The oxide-supported Pt nanoparticle (NP) catalysts can enhance the utilization efficiency of Pt and improve the stability of Pt NPs by fabrication of metal-oxide/support interface structures, which are the active sites of O 2 adsorption–activation due to the strong Pt–oxide interaction. …”
Section: Introductionmentioning
confidence: 99%
“…After the catalysts were exposed in the test gases, the bands located at 1364 cm −1 , 1566 cm −1 , 1660 cm −1 , 1780 cm −1 , 2340 cm −1 , 3252 cm −1 , and 3730 cm −1 were observed in both of the spectra. According to the previous literature, the bands at 1364 cm −1 and 1660 cm −1 were ascribed to the asymmetric vibration and symmetric strength of formate, respectively [36,37]. The band at 1566 cm −1 was assigned to the surface carbonate from the oxidation of formate over the catalysts [7,37].…”
Section: Resultsmentioning
confidence: 95%
“…3734 cm −1 and 3252 cm −1 corresponding to hydroxyl were attributed to the isolated OH group of formic acid, and the surface OH groups that were bonded to the catalyst overlapped with the groups from the water in air, respectively [30,38]. In addition, the formation of CO 2 was observed too by the band at 2340 cm −1 , whereas the signal of CO (the band at 2042 cm −1 ) was not observed [7,37]. Hence, it was suggested that HCHO conversion over these two catalysts both followed a pathway of the direct formate oxidation.…”
Section: Resultsmentioning
confidence: 99%